Napredek in izzivi v razvoju živih bioterapevtskih izdelkov - Grilc, Nina Katarina (Farmacevtski vestnik, 2024)
The skin and mucous membranes are inhabited by microbiota, which play a crucial role in maintaining health, as its imbalance can lead to various diseases. Probiotics contribute to restoring microbiota balance through mechanisms such as inhibiting pathogen colonization, modulating the immune system, and strengthening the protective function of mucous membranes. This paper discusses traditional probiotics as well as next-generation probiotics designed for use in live biotherapeutic products. Their development requires appropriate strain selection, specific characterization, drying method optimization, and formulation adaptation for each strain. A quality probiotic product must contain sufficient live bacteria that retain their biological activity from incorporation into the formulation, through storage, to delivery at the target site. Despite fast scientific advances, ensuring the high survival rate of some strains remains a technological challenge addressed in the present article. Next-generation probiotics hold great promise for the prevention and treatment of some infectious and inflammatory diseases, as evidenced by intensive research in this field.
Keywords: drying; encapsulation; enkapsulacija; formulation design; live biotherapeutic products; načrtovanje formulacij; probiotic testing; probiotics; Probiotiki; sušenje; testiranje probiotikov; živi bioterapevtski izdelki